The Complete Plastome Sequences of Four Orchid Species: Insights into the Evolution of the Orchidaceae and the Utility of Plastomic Mutational Hotspots - Niu, Zhitao; Xue, Qingyun; Zhu, Shuying; Sun, Jing; Liu, Wei; Ding, Xiaoyu (Frontiers in Plant Science, 2017)
Orchidaceae (orchids) is the largest family in the monocots, including about 25,000 species in 880 genera and five subfamilies. Many orchids are highly valued for their beautiful and long-lasting flowers. However, the phylogenetic relationships among the five orchid subfamilies remain unresolved. The major dispute centers on whether the three one-stamened subfamilies, Epidendroideae, Orchidoideae, and Vanilloideae, are monophyletic or paraphyletic. Moreover, structural changes in the plastid genome (plastome) and the effective genetic loci at the species-level phylogenetics of orchids have rarely been documented. In this study, we compared 53 orchid plastomes, including four newly sequenced ones, that represent four remote genera: Dendrobium, Goodyera, Paphiopedilum, and Vanilla. These differ from one another not only in their lengths of inverted repeats and small single copy regions but also in their retention of ndh genes. Comparative analyses of the plastomes revealed that the expansion of inverted repeats in Paphiopedilum and Vanilla is associated with a loss of ndh genes. In orchid plastomes, mutational hotspots are genus specific. After having carefully examined the data, we propose that the three loci 5′trnK-rps16, trnS-trnG, and rps16-trnQ might be powerful markers for genera within Epidendroideae, and clpP-psbB and rps16-trnQ might be markers for genera within Cypripedioideae. After analyses of a partitioned dataset, we found that our plastid phylogenomic trees were congruent in a topology where two one-stamened subfamilies (i.e., Epidendroideae and Orchidoideae) were sisters to a multi-stamened subfamily (i.e., Cypripedioideae) rather than to the other one-stamened subfamily (Vanilloideae), suggesting that the living one-stamened orchids are paraphyletic.